2007
DOI: 10.1111/j.1532-5415.2007.01418.x
|View full text |Cite
|
Sign up to set email alerts
|

Serum Calcium and Cognitive Function in Old Age

Abstract: In the general population, high serum calcium levels are associated with faster decline in cognitive function over the age of 75.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
41
1
1

Year Published

2008
2008
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(45 citation statements)
references
References 30 publications
2
41
1
1
Order By: Relevance
“…In the Rotterdam study on cognitive function in 3994 individuals between ages 55 and 90 years, high serum calcium was significantly associated with worse global cognitive function during a median follow-up of 11 years. 22 In the present study, high calcium levels in patients with pHPT correlated significantly with higher HADS depression scores, more severe depressive symptoms, and suicidal ideation on the PHQ-9, as well as reduced SF-36 mental health scores. No such correlation was seen in the control group.…”
Section: Commentsupporting
confidence: 59%
“…In the Rotterdam study on cognitive function in 3994 individuals between ages 55 and 90 years, high serum calcium was significantly associated with worse global cognitive function during a median follow-up of 11 years. 22 In the present study, high calcium levels in patients with pHPT correlated significantly with higher HADS depression scores, more severe depressive symptoms, and suicidal ideation on the PHQ-9, as well as reduced SF-36 mental health scores. No such correlation was seen in the control group.…”
Section: Commentsupporting
confidence: 59%
“…The study results about the relationship between calcium and cognitive function are also inconsistent. High calcium levels have been reported to result in accumulation of calcium in brain cells and nerve cells, causing cell necrosis and adversely affecting cognitive function, whereas a large cohort study of 2,000 Chinese showed that the higher the calcium level, the better cognitive function [16,17]. In Korea, a study of 38 Alzheimer's patients aged 65 years or older reported that calcium had a negative effect on cognitive function [18].…”
Section: The Need For Researchmentioning
confidence: 99%
“…Further antioxidants may be also part of a functional neuroplastic diet, such as choline, combination of vitamins [C, E, carotene], calcium, selenium, zinc and creatine, which delay brain decline, promote longevity and cellular energetic nerve tissues storage and repair etc. [54][55][56][57][58].…”
Section: Other Antioxidant Nutrientsmentioning
confidence: 99%